Measuring the Effectiveness of Arabic Immersion: A Critical Evaluation of the CIPP Model in the PBA International Class at UIN Sunan Kalijaga - Bahtiar, Muchtar Firdaus; Maksudin, Maksudin (Pusdikra Publishing, 2025)
This study aims to determine the effectiveness of the Arabic immersion program in improving the language proficiency of international class students of PBA study program at UIN Sunan Kalijaga Yogyakarta with the CIPP model. The research method used is qualitative with case study analysis that focuses on the effectiveness of the immersion method implemented. Data were obtained using in-depth interviews, observation and documentation and analyzed inductively. The results of the CIPP evaluation holistically show that the immersion program in international classes is effective for improving competence, it is shown that the context analysis confirms the suitability of the program with academic needs, input/ input evaluation shows good human resource readiness, although there are some technical shortcomings, process evaluation shows implementation in accordance with the principles of immersion, while product evaluation shows an increase in student skills.